Ice breaking in GPCR structural biology - Zhao, Qiang (Nature Publishing Group, 2012)
G-protein-coupled receptors (GPCRs) are one of the most challenging targets in structural biology. To successfully solve a high-resolution GPCR structure, several experimental obstacles must be overcome, including expression, extraction, purification, and crystallization. As a result, there are only a handful of unique structures reported from this protein superfamily, which consists of over 800 members. In the past few years, however, there has been an increase in the amount of solved GPCR structures, and a few high-impact structures have been determined: the peptide receptor CXCR4, the agonist bound receptors, and the GPCR-G protein complex. The dramatic progress in GPCR structural studies is not due to the development of any single technique, but a combination of new techniques, new tools and new concepts. Here, we summarize the progress made for GPCR expression, purification, and crystallization, and we highlight the technical advances that will facilitate the future determination of GPCR structures.